Simulation of microtube irradiation on the beam tubes of GA Siwabessy reactor for in-vitro boron neutron capture therapy. Issue 1 (June 2021) - Rasito,; Su'ud, Z; Permana, S
Abstract: The BNCT in-vitro test using a microtube irradiated in the neutron beam of the RSG-GAS beam tubes has been simulated using PHITS code. The simulation was performed by modeling a microtube containing boron solution which was placed 5 cm in front of the beam tubes. Inside the beam tube was installed a beam shaping assembly (BSA) using 80 cm of MgF 2 as a filter to reduce fast neutron and gamma fluences. Microtube containing 1.5 mL of boron solution with boron enriched 10 B of 90%. The microtube dose i.e alpha dose, 7 Li dose, proton dose, and gamma dose were calculated for boron concentration of 1 ppm. The simulation of microtube containing 1 ppm boron solution shown that irradiated in the BSA-S5 neutron beam can produce 20 Gy dose in the shortest irradiation time of 2.5 hours.